Evaluation of Antimicrobial Activity of Ruta graveolens Stem Extracts by Disc Diffusion Method - Hajra, Pinkee Pandey*, Archana Mehta, Subhadip (Journal of Phytology, 2011)
In the present study, we evaluated the antimicrobial activity of ethanolic, methanolic, chloroform and water extracts of Ruta graveolens stem against Escherichia coli (MTCC 40), Pseudomonas aeruginosa (MTCC 424), Klebsiella pneumoniae (MTCC432), Staphyloccous aureus (MTCC 96), Bacillus subtilis (MTCC 619), Salmonella typhimurium (MTCC 98) and Aeromonas culicicola (MTCC 3249) as well as fungi such as Aspergillus niger, Aspergillus flavus, Penicilium crysogenum, Rhizopus stolonifer and Fusarium oxosporium by agar-disc diffusion and (MIC) method. The ethanolic stem extract showed pronounced inhibition of growth than other extracts. The ethanolic extract showed most susceptible activity against S. aureous and B. subtilis (zone of inhibition was 22.0±0.04mm and19.4±0.24mm) where as P. aeruginosa (Zone of inhibition was 12.5±0.17mm) was the most resistant bacterial strain at a concentration of 100µg/ml. All the extract showed moderate antifungal activity except Fusarium oxosporium. Phytochemical analysis showed mainly the presence of alkaloids and steroids, which may the active compounds.